Answer:
The quadratic equation is
![f(x) = 2x^2 + 6x + 4](https://img.qammunity.org/2022/formulas/mathematics/college/tz8qmudujinio71nk9avxuddpaglso5qsq.png)
Explanation:
Zeros of a function:
Given a polynomial f(x), this polynomial has roots
such that it can be written as:
, in which a is the leading coefficient.
Roots are -2 and -1 and the leading coefficient 2
This means that
![x_1 = -2, x_2 = -1, a = 2](https://img.qammunity.org/2022/formulas/mathematics/college/zrf65933k36n10xyzjlzvijt625dp111y5.png)
So
![f(x) = 2(x - (-2))(x - (-1)) = 2(x + 2)(x + 1) = 2(x^2 + 2x + x + 2) = 2(x^2 + 3x + 2) = 2x^2 + 6x + 4](https://img.qammunity.org/2022/formulas/mathematics/college/5t4coiusxcbc962wcs9v2fqy080xrv1p5p.png)
The quadratic equation is
![f(x) = 2x^2 + 6x + 4](https://img.qammunity.org/2022/formulas/mathematics/college/tz8qmudujinio71nk9avxuddpaglso5qsq.png)